Copy book containing an account by John Logan of his experiences as an Irish prisoner in 1916, titled 'Experiences of one of the Irish Prisoners in 1916. By one who was there', with letter to the editor of a publication, - Logan, John Baltimore, County Cork (1960)
Describes his arrest, trial and imprisonment at Wandsworth Prison.